An efficient replica placement strategy in highly dynamic data grids. (8th June 2011) - Ben Charrada, Faouzi; Ounelli, Habib; Chettaoui, Hanene
Data grids are an emerging new technology for managing large amounts of distributed data. This technology is highly used by the large-scale data-intensive applications. Because data is the important resource in data grids, an efficient management is needed to minimise the response time of applications. Replication is typically used in data grids to improve access time and to reduce the bandwidth consumption. In this paper, we propose a new replication strategy for highly dynamic data grids which takes into account the dynamicity of sites. Indeed, the dynamicity of sites is an important challenge in grids. Our strategy helps to increase file availability, to improve the response time and to reduce the bandwidth consumption. We evaluate our strategy through simulation using OptorSim. The results we have obtained seem to be promising.